Response to sequential treatment with prednisolone and vigabatrin in infantile spasms. (24th August 2022) - Dzau, Winston; Cheng, Sally; Snell, Penny; Fahey, Michael; Scheffer, Ingrid E; Harvey, A Simon; Howell, Katherine B
Abstract : Aim: To report response to first treatment in infants with infantile spasms (IS), including incremental benefit of prednisolone 60 mg/day and vigabatrin following prednisolone 40 mg/day failure in infants commenced on the United Kingdom Infantile Spasms Study (UKISS) treatment sequence. Methods: In this retrospective analysis, we compared effectiveness of prednisolone, vigabatrin and nonstandard treatments as first treatment for IS. In infants who commenced the UKISS treatment sequence, we evaluated response to each step. Primary outcome was spasm cessation after 42 days. Secondary outcomes were severe side effects and spasm relapse after 42 days. Results: Treatment response data were available for 151 infants. First treatment was prednisolone in 99 infants, vigabatrin in 18 and nonstandard treatment in 34. The rate of spasm cessation with first treatment was significantly higher with prednisolone (62/99, 63%) than vigabatrin (5/18, 28%, P  = 0.01) or nonstandard treatment (2/34, 5.9%, P  < 0.01). Of 112 infants who commenced the UKISS treatment sequence, 71/112 (63%) responded to prednisolone 40 mg/day. Among non‐responders, 12/29 (41%) subsequently responded to prednisolone 60 mg/day, and 10/22 (45%) to vigabatrin. Severe side effects and spasm relapse were not significantly different between each treatment. Conclusion: We confirm higher rates of spasm cessation with initial treatment with prednisolone than vigabatrin and nonstandard therapy. Non‐use of prednisolone as first treatment in over one third of infants highlights a concerning treatment gap. The UKISS treatment sequence has high overall treatment response (total 93/112; 83%), with similar benefit of subsequent prednisolone 60 mg/day and vigabatrin in prednisolone 40 mg/day non‐responders.